Question:
![\frac{sin(A - B)}{cosAcosB} + \frac{sin(B- C)}{cosBcos C} + \frac{sin(C - A)}{cosC - cosA} = 0 \frac{sin(A - B)}{cosAcosB} + \frac{sin(B- C)}{cosBcos C} + \frac{sin(C - A)}{cosC - cosA} = 0](https://tex.z-dn.net/?f=+%5Cfrac%7Bsin%28A+-+B%29%7D%7BcosAcosB%7D++%2B++%5Cfrac%7Bsin%28B-+C%29%7D%7BcosBcos+C%7D++%2B++%5Cfrac%7Bsin%28C+-+A%29%7D%7BcosC+-+cosA%7D++%3D+0)
Answers
Answered by
12
See the attachment I think it will help you^_^
✴ Here we use ,
✴Sin ( A-B)=Sin A Cos B -CosA SinB
similarly,
✴Sin ( B-C)=Sin B Cos C-CosB SinC
✴Sin(C-A) = Sin C Cos A -Cos C Sin A
THANKS ❤^_^
#RÔYÂL CHÔRÎ ♥
Attachments:
![](https://hi-static.z-dn.net/files/d14/d6f121f7bed0a42c4d89deb6d0f83d11.jpg)
Answered by
7
=
Using the Identity,
sin(A - B) = Sin A Cos B - Cos A Sin B
=
=
=
=
✓✓✓
✌
Similar questions